RELEVANSI KEHARAMAN BERTATO DENGAN LARANGAN DONOR DARAH BAGI ORANG BERTATO - Nasution, Muhammad Arsad; Siregar , Rosnani; Baharuddin, Didin (TAHKIM, 2024)
Tattooing is a part of art that many people do. However, Islamic law prohibits people with tattoos, on the other hand, medical science also prohibits people with tattoos from donating blood. This article tries to explain whether there is a match (relevance) between the prohibition of tattooing according to Islamic law and the prohibition of blood donation for people with tattoos according to medical science. To answer this question, the author collects data from various sources of scientific writings in the form of books or journals that describe the prohibition of tattooing according to Islamic law and also scientific writings related to the prohibition of blood donation for people with tattoos according to health. This disclosure is important to explore to uncover the maqasid al-syari' in prohibiting the act of tattooing according to Islamic law. The results obtained from the scientific data above show that the Prophet Muhammad forbade his people from getting tattoos. This prohibition is stated in several hadiths of the Prophet Muhammad with a clear prohibition expression, namely using the phrase "la'ana" (Allah/Rasulullah curses). The use of this phrase for a legal act, namely getting a tattoo, shows that the act is forbidden. Medical also prohibits blood donation for people with tattoos, this is because the behavior of sticking needles and alcohol into the pores of the body is an act of damaging body parts. The reason for the medical prohibition for people with tattoos to donate blood is also the concern of contracting various diseases in the blood cells of people with tattoos caused by the needle being inserted into the blood vessels through the skin, and the entry of other substances into the blood cells. The prohibition of tattoos by the Prophet Muhammad SAW turns out to be in accordance with medical science which prohibits people with tattoos from donating blood. This conformity can be seen in the principles of Islamic law which forbids harmful acts, and medical also positions the act of tattooing as having harm. Keywords: Relevance, islamic law, tattooed, blood donation